A szabadságharc ritualizált emlékezete Debrecenben: Szimbolikus térfoglalás a perifériától a belvárosig (1849−1902) - Fazakas, Gergely Tamás (Studia Litteraria, 2021)
My study focuses on the local memory of the Hungarian Revolution and War of Independence of 1848–1849 in the city of Debrecen. I examine how the annual ceremonies on the days of remembrance, and the meaning of monuments changed in the second half of the nineteenth century in Debrecen: on the Day of the Revolution (15th of March), on the anniversary of the lost Battle of Debrecen in 1849 (2nd of August), and on the memorial day of the political martyrs of Hungary (6th of October). Public commemorations on these days were prohibited during the first few years after the repression of the War of Independence. I argue that ritual remembrance of the Hungarian Revolution from the 1850s to 1902, and erecting memorials after the Austro-Hungarian Compromise of 1867 was a symbolic placetaking process in the urban space of Debrecen, and in other cities of Hungary. One can trace this progress from the repression of remembrance to the community fiesta of the local society on the map of Debrecen: from the Western and Eastern periphery of the city (burial places of the heroes of the war) to the city centre (Memorial Garden, High Street, Town Hall).